Psychological support in postoperative pain management in patients with maxillofacial fractures - D. Semenov (Journal of Education, Health and Sport, 2019)
Relevance. Psychological distress in persons with maxillofacial area fractures are not sufficiently developed in key of their influence on postoperative pain intensity, patients interpersonal sensitivity and emotional reactions. In the context of maxillofacial reconstructive surgery the psychological support of patients is promising direction to improve the condition of patients in postoperative period. The aim: to determine the effect of psychological support on the intensity and additional characteristics of postoperative pain in patients with maxillofacial fractures. Materials and metods. 120 patients with maxillofacial area fractures, undergoing reconstructive surgery at Municipal Clinical Hospital of Emergency and Rapid Care (Zaporizhzhya, Ukraine) were examined. The study was performed on 2 parallel groups, by 60 patients in each. Patients of the main group underwent original model of psychological support and standard postoperative treatment, patients of control group underwent only standard postoperative treatment. Clinical, radiological, psychological and statistical methods were used. Results. The normalization of patient’s psychological response to postoperative pain and rational perception of physical discomfort were found. Conclusion. The original model of psychological support in the postoperative period of reconstructive surgical interventions for maxillofacial fractures reduces the subjective intensity of postoperative pain among the contingent of patients.